Overview of the Development of Language Skills in Toddlers with Prescreening Developmental Questionnaire (PDQ) at Posyandu Anggrek Sukamandi, Sagalaherang District, Subang, Indonesia - Sutarman, Noventy (Open Access Indonesian Journal of Medical Reviews, 2023)
At the toddler development stage, namely 1-3 years old, language skills become a very crucial aspect in the process of interaction and communication with the surrounding environment. At this time, children begin to develop vocabulary, speech skills, understand instructions, and express themselves using words. This study aimed to provide an overview of the development of language skills in toddlers at Posyandu Anggrek Sukamandi, Sagalaherang District, Subang, Indonesia. This study was a descriptive observational study. A total of 42 research subjects participated in this study. Univariate analysis was carried out to screen language skills with the PDQ. Toddlers who experience questionable language development are 7.14%. Toddlers with adverse language development were found in 28.57% of toddlers with malnutrition and 3.23% of toddlers with good nutrition, 16.67% of toddlers with mothers who had primary school education, and 7.15% of toddlers with mothers who had a junior high school education. The percentage of the development of questionable language is higher in toddlers who have risk factors than in toddlers who don't have risk factors.